The Concept of Narimo Ing Pandum towards Dokar's Coachmens - Primadita Yemimaistyasih (Universitas Ciputra Surabaya, 2022)
Increasingly, competition for work had an impact on dokar coachman. The coachers have trouble obtaining passengers and earning a daily income. In fact, it wasn’t uncommon for them to bring no income at all. Nowadays, some of the jobs that are available require workers to understand the technology, whereas coachmen haven’t kept up with the development of technology from a young age to have insufficient competitiveness to choose other employment opportunities. It’s also affected by the limitations of the physical and economic abilities of the coachmen. Therefore, the coachmen prefer to pursue his work as a driver in order to keep the family’s needs kosher. The aim of this study is to get to know the pictures and ways that the ethical coachmen in Salatiga to the concept of “narimo ing pandum”. The study employs qualitative methods using data retrieval techniques through interviews, observation, and documentation. The study explains that 2 out of 3 participants already had the concept of “narimo ing pandum” as a form of acceptance with what is, accepting what is, always grateful, and relying on god YME in every way. In summary, all of the participants had a way of reconnecting the philosopy concept of “narimo ing pandum”. Key words: narimo ing pandum, coachmen, dokar